The proportion of COVID-19 cases that are asymptomatic in South Korea: Comment on Nishiura et al. (July 2020) - Workman, Joseph
Highlights: The Korean Centers for Disease Control & Prevention reports the asymptomatic case proportion for COVID-19 is 33.3%. The asymptomatic case proportion in South Korea closely approximates the rate of 30.8% reported by Nishuara et al. (2020). The asymptomatic case proportion in South Korea is higher (56.1%) among those who re-test positive for COVID-19. Abstract: The Korean Centers for Disease Control & Prevention reports the asymptomatic case proportion for COVID-19 is 33.3%. The asymptomatic case proportion in South Korea closely approximates the rate of 30.8% reported by Nishiura et al. (2020) among Japanese nationals returning from abroad.